2014
DOI: 10.18632/oncotarget.2861
|View full text |Cite
|
Sign up to set email alerts
|

A novel antisense long noncoding RNA regulates the expression of MDC1 in bladder cancer

Abstract: Antisense long noncoding RNAs (lncRNAs) play important roles in regulating the expression of coding genes in post-transcriptional level. However, detailed expression profile of lncRNAs and functions of antisense lncRNAs in bladder cancer remains unclear. To investigate regulation of lncRNAs in bladder cancer and demonstrate their functions, we performed lncRNAs microarray analysis in 3 paired bladder cancer tissues. Further molecular assays were conducted to determine the potential role of identified antisense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 32 publications
(31 reference statements)
2
44
0
Order By: Relevance
“…Derrien et al [6] also reported a majority of positive co-expressions for lncRNA-mRNA pairs in an anti-sense orientation. The mechanisms that underlie such positive co-expression seem to be complex and act at distinct regulatory levels including the translation, splicing and transcription levels [5558]. …”
Section: Resultsmentioning
confidence: 99%
“…Derrien et al [6] also reported a majority of positive co-expressions for lncRNA-mRNA pairs in an anti-sense orientation. The mechanisms that underlie such positive co-expression seem to be complex and act at distinct regulatory levels including the translation, splicing and transcription levels [5558]. …”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have revealed that lncRNAs were found to be deregulated in several human cancers including bladder cancer [15,16]. Understanding the molecular mechanism of lncRNAs may help to explore new promising therapeutic strategy for the treatment of bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…9 Additionally, different classes of lncRNAs can regulate critical cancer genes through a variety of mechanisms. For instance, antisense lncRNAs typically regulate protein-coding genes in close proximity 60,61 whereas cytoplasmic competing endogenous RNAs (ceRNAs) will compete with cancer genes harboring similar microRNA binding sites to modulate expression. 62 Therefore, given the broad and expanding range of lncRNA functions, our comprehensive study importantly hones in on critical onco-lncRNAs and provides an initial framework for dissecting their emerging regulatory roles with oncogenes and tumor suppressors.…”
Section: Discussionmentioning
confidence: 99%